5-6 GRADES EXAMPLE GEOMETRIC CONCEPTS AT SCHOOL INNOVATIVE APPROACH TO LEARNING - Sevara Akbarova Husanboy qizi, Nafisa Tohtasinova Imomovna (American Journals, 2023)
The article discusses the possibilities of using innovative pedagogical technologies in teaching geometry in grades 5-6 and their classification. The role of studying geometric material in mathematics lessons is characterized. Some types of pedagogical technologies from this classification are also highlighted. As a result, we analyzed the implementation of innovative pedagogical technologies in the study of geometry in grades 5-6 of secondary school.
Keywords: Teaching, geometry, innovative pedagogical technologies, educational process, innovative learning, teaching method.